2013
DOI: 10.9775/kvfd.2013.8442
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Passive Immunity, Health, Birth Weight and Growth Performance in Lambs: II. Effects of Passive Immunity and Some Risk Factors on Growth Performance During the First 12 Weeks of Life

Abstract: SummaryThe primary objective of this study was to evaluate the relationship between passive immunity and growth performance in lambs in neonatal and post-neonatal periods. The study also evaluated the effect of gender, type of birth, birth weight and health of lambs, lambing season and dam's age on growth performance. This study included two crossbred Akkaraman flocks (n=301) in Kars, Turkey. The results disclosed that serum IgG concentration determined at 24 th of birth (SIgG-24) was significantly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(67 reference statements)
1
9
0
1
Order By: Relevance
“…PTS determination of newborns is also valuable in routine herd health programs, observation during disease investigations and in the assessment of individual neonates with questionable colostral intake [8,9,24] . Passive transfer of immunity prevents disease and enhances growth performance not only in the short term, such as in neonatal period, but also in the long term, such as the post-weaning period in lambs [5,8,9,18,27] . Inadequate PTS may not be effect health provided that sanitation is excellent, but adequate PTS may be sufficient even if poor sanitation and extreme infectious pressure exist [8,9,27] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PTS determination of newborns is also valuable in routine herd health programs, observation during disease investigations and in the assessment of individual neonates with questionable colostral intake [8,9,24] . Passive transfer of immunity prevents disease and enhances growth performance not only in the short term, such as in neonatal period, but also in the long term, such as the post-weaning period in lambs [5,8,9,18,27] . Inadequate PTS may not be effect health provided that sanitation is excellent, but adequate PTS may be sufficient even if poor sanitation and extreme infectious pressure exist [8,9,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Zinc sulfate turbidity (ZST) test was utilized and the results were designated by several researchers as <12 [12] and <20 units [15] in 1-to 2-day-old lambs. The model predicting STPC based on ZST units for 1-day-old lambs revealed that STPC of 5.2 and 5.4 g/dL were equivalent to 10 and 12 ZST units, respectively [18] . This was the only study exist in the literature relating STPC with neonatal diseases in lambs and no STPC threshold was used for morbidity risk.…”
Section: Gökçe Ataki̇şi̇mentioning
confidence: 99%
See 2 more Smart Citations
“…Alguns outros fatores também podem levar à falha na transferência de imunidade passiva, como ocorre em casos de ovelhas primíparas ou mais velhas, de partos gemelares (Halliday 1976, Hunter et al 1977, McGuire et al 1983, Bekele et al 1992, Christley et al 2003, de parições durante o inverno (Gokçe et al 2013), por desnutrição das ovelhas durante a gestação (Halliday 1978, Mellor & Murray 1985, 1986, pelo nascimento de cordeiros prematuros ou com baixo peso ao nascimento (Gokçe et al 2013). Portanto, é de extrema importância o reconhecimento desses fatores, pois pode fornecer bases e fundamentos para a adoção de medidas preventivas que evitem ou diminuam a incidência dessa condição em um rebanho.…”
Section: Introductionunclassified